Vlogging as an Assessment Tool in ELT: A Study Among Adult Learners in a Distance Learning Programme - Manan, Nor Ashikin Ab; Azizan, Noraziah (Elsya : Journal of English Language Studies, 2022)
The study was conducted to address the problem of English language speaking anxiety among adult ESL learners by introducing vlogging as one of the learning activities and as an assessment of speaking skills. The main objective of this action research was to establish whether vlogging assignments could assist in alleviating speaking anxiety among adult learners and in determining whether the students' vlogs posted in the class's Facebook group could be used as part of the course's speaking assessment to replace face-to-face presentation. A qualitative research design was adopted in this study. The study employed purposeful sampling, and the participants chosen came from an intact group of thirty adult learners who enrolled in a distance learning programme at a public university in Malaysia. The study was conducted in the students’ ‘English for Communication’ class over a study period of fourteen weeks. The data was collected at the end of the study period through focused group interviews and analysed using the thematic analysis method, and presented descriptively. It was found that vlogging is effective in increasing the students’ English talk time outside class which consequently contributes to increasing their self-confidence and alleviating speaking anxiety. Thus, it can be concluded that vlogging is effective in lessening language speaking anxiety among the participants and can effectively be used as an assessment tool to reduce test-taking anxiety. Facebook group is also found to be a suitable platform for group interactions as it provides a non-threatening learning environment for the learners. The findings of the study have potential implications for English language teaching among adult learners.